The Effect Of Coretax Knowledge On The Compliance Of Sharia MSME Taxpayers In Cirebon City - Chasan Bisri; Bahtiar Bahtiar; Yusuf Yusuf (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Taxpayer compliance is a crucial factor in increasing state revenue, particularly from the Micro, Small, and Medium Enterprises (MSMEs) sector. Along with the implementation of the Core Tax Administration System (Coretax), taxpayers’ understanding of this system has become an important determinant of successful tax compliance. This study aims to analyze the effect of Coretax knowledge on MSME taxpayer compliance in Cirebon City. This research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 50 MSME taxpayers, selected using accidental sampling techniques. The research instruments were tested for validity and reliability, and the results confirmed that all questionnaire items were valid and reliable. Data analysis was conducted using simple linear regression analysis with the assistance of SPSS software. The findings indicate that Coretax knowledge has a positive and significant effect on MSME taxpayer compliance. This result suggests that a higher level of understanding of the Coretax system enhances MSME taxpayers’ ability to fulfill their tax obligations, including accurate tax reporting and timely tax payments. Adequate knowledge of Coretax helps reduce administrative errors and increases taxpayers’ awareness and willingness to comply with applicable tax regulations. The results of this study contribute to the development of tax compliance literature and provide practical implications for the Directorate General of Taxes in designing effective Coretax education and socialization programs to improve MSME taxpayer compliance.